The creation and training of how to calculate the Break-Even Point (B.E.P) in Micro, Small, and Medium Enterprises (UMKM) in Margamulya, Bekasi - Angkasa, Zeno (Yayasan Putra Adi Dharma, 2023)
This study focuses on the development and training of Break-Even Point (B.E.P) calculation methods for Micro, Small, and Medium Enterprises (UMKM) located in Margamulya, Bekasi. The Break-Even Point is a crucial financial indicator for businesses as it signifies the point at which total revenues equal total costs, indicating the threshold for profitability. In the context of UMKM, understanding and effectively calculating the B.E.P is fundamental for informed decision-making and sustainable growth. The research outlines the creation of accessible and practical B.E.P calculation tools tailored to the specific needs and characteristics of UMKM in Margamulya. Additionally, a comprehensive training program is designed to equip UMKM entrepreneurs with the necessary skills and knowledge to utilize these tools effectively. Preliminary results indicate improved financial management and decision-making among UMKM in Margamulya. The findings emphasize the significance of empowering UMKM with financial literacy and tools to enhance their long-term viability and competitiveness. This study contributes to the broader discourse on supporting the growth of small enterprises, underlining the importance of financial knowledge and tools in fostering economic sustainability within local communities.